2009
DOI: 10.1002/art.24772
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic signs and symptoms in fibromyalgia

Abstract: Objective. To determine the type and frequency of neurologic signs and symptoms in individuals with fibromyalgia (FM).Methods. Persons with FM (n ‫؍‬ 166) and painfree controls (n ‫؍‬ 66) underwent systematic neurologic examination by a neurologist blinded to disease status. Neurologic symptoms lasting at least 3 months were assessed with a standard questionnaire. We used logistic regression to evaluate the association of neurologic symptoms and examination findings with FM status. Within the FM group we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 13 publications
4
60
0
3
Order By: Relevance
“…[42] In addition to FM, Irritable Bowel Syndrome, tension-type headaches, interstitial cystitis, temporomandibular joint disease (TMD), chronic fatigue syndrome, and possibly restless leg syndrome are thought to be sensory hypersensitivity conditions ( Figure 1). [43][44][45][46] These conditions often share features typical of FM including diffuse pain in multiple body regions, fatigue, sleep disorders, memory difficulties, mood disturbance, individual or familial history of chronic pain, and increased sensitivity to sensory input in the presence of an otherwise generally normal physical examination. Furthermore, sensory hypersensitivity conditions often copresent with each other suggesting a possible common pathogenesis.…”
Section: Understanding Chronic Painmentioning
confidence: 99%
“…[42] In addition to FM, Irritable Bowel Syndrome, tension-type headaches, interstitial cystitis, temporomandibular joint disease (TMD), chronic fatigue syndrome, and possibly restless leg syndrome are thought to be sensory hypersensitivity conditions ( Figure 1). [43][44][45][46] These conditions often share features typical of FM including diffuse pain in multiple body regions, fatigue, sleep disorders, memory difficulties, mood disturbance, individual or familial history of chronic pain, and increased sensitivity to sensory input in the presence of an otherwise generally normal physical examination. Furthermore, sensory hypersensitivity conditions often copresent with each other suggesting a possible common pathogenesis.…”
Section: Understanding Chronic Painmentioning
confidence: 99%
“…56 Similarly, the fibromyalgia patients from the Oslo Health Study reported symptomatic dizziness or faintness within the last week 59.3% of the time versus 26% for those without fibromyalgia. 57 An independent relationship persisted after adjustment for gender, age, comorbid conditions, and use of medications, with fibromyalgia patients having 1.92 higher odds of dizziness and faintness (95% confidence interval 1.62-2.28).…”
Section: Fibromyalgiamentioning
confidence: 98%
“…Bu hastalar sıklıkla boyundan kola doğru yayılan uyuşukluk, duyu bozukluğu, ağrı gibi şikayetlerden yakınırlar. Bu nedenle FMS sıklıkla periferik nöropati, tuzak nöropatiler gibi nörolojik bozukluklarla karışabilmektedir (59). Ayrıntılı bir nörolojik muayene ile birlikte eşlik edebilecek yorgunluk, duygudurum ve uyku bozuklukları gibi overlap sendromların araştırılması ayırıcı tanıda ileri tetkik istemeden önce yardımcı olabilir.…”
Section: Fibromiyalji̇ Sendromu (Yumuşak Doku Romati̇zmasi)unclassified